2022
DOI: 10.1111/aas.14071
|View full text |Cite
|
Sign up to set email alerts
|

Pupil response to painful stimuli during inhalation anaesthesia without opioids in children

Abstract: Background: Pupil dilation reflex measured by a pupillometer is known to be a useful parameter for assessing the response to perioperative noxious stimuli. In children, pupillometer can reflect changes after painful stimuli during anaesthesia or guide anaesthesia to reduce opioid consumption. However, to date, there are no data regarding pupil response during inhalation anaesthesia with analgesia by intravenous acetaminophen in children. Methods:We planned a prospective, single-armed study of children aged bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition, a pupillometer can guide postoperative analgesia 27 . The change of NPi, one of the indicators to evaluate pupil reactivity through pupillary light reflex, was observed in anesthetized pediatric patients with noxious stimulation 21,28 . Furthermore, it has been reported that NPi differed depending on the type of anesthetic in adult patients undergoing general anesthesia 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a pupillometer can guide postoperative analgesia 27 . The change of NPi, one of the indicators to evaluate pupil reactivity through pupillary light reflex, was observed in anesthetized pediatric patients with noxious stimulation 21,28 . Furthermore, it has been reported that NPi differed depending on the type of anesthetic in adult patients undergoing general anesthesia 18 .…”
Section: Discussionmentioning
confidence: 99%
“…As assumed in the previous study, this may be because the rapid dilation of the pupil diameter affects the calculation formula of NPi. 21 Since the emergence profiles of sevoflurane and propofol are different in terms of postoperative nausea and vomiting or emergence agitation, further studies are required on the mechanisms underlying the differences in emergence profiles between propofol and volatile anesthetics and their effects on pupillary or midbrain function. The CV and DV were both affected by the type of anesthetic agent used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of pain on pupil size were described already more than a century ago (Bumke, 1911) and have been reported in a variety of populations (Drummond & Clark, 2023;Ji et al, 2022;Macchini et al, 2022;Sillevis et al, 2021;Yılmaz, 2022). Only a few modern-day studies have directly investigated the effects of non-painful tactile stimulation on pupil size, mostly in animals (Gusso et al, 2021).…”
Section: Introductionmentioning
confidence: 99%